Forest degradation and its expression in the territory of Republic of Armenia - M. S. Khechoyan (ՀՀ ԳԱԱ հրատ.)
The article refers to the issue of forest degradation, the analysis of the main factors causing degradation, the reasons for the degradation of the forests of Armenia, the current state and the restoration means of degraded forests in Armenia. At present the degradation of forests is one of the most important and urgent problems mankind faces, the main reason for which is human being's irrational and non-professional nature. The main reason for the degradation of forests in Armenia is the human factor, especially illegal logging of the 1990s. The restoration of degraded forests is based on the following methods: natural growth support by fencing, natural re-growth support through soil mineralization, coppicing, etc. Ներկայումս անտառների դեգրադացիան մարդկության առջև ծառացած կարևոր և հրատապ լուծում պահանջող հիմնախնդիրներից մեկն է, որի գլխավոր պատճառը մարդու ոչ ռացիոնալ և անհաշվենկատ բնօգտագործումն է: ՀՀ-ում անտառների դեգրադացման գլխավոր պատճառը նույնպես մարդկային գործոնն է, հատկապես 1990-ական թթ. ապօրինի անտառահատումները: Դեգրադացված անտառների վերականգնումը հիմանակնում կատարվում է հետևյալ եղանակներով՝ բնական վերաճի օժանդակում ցանկապատման եղանակով, բնական վերաճի օժանդակում հողի հանքայնացման եղանակով, կոճղաշիվային վերաճի օժանդակում և այլն: Рассматривается проблема деградации лесов Республики Армения и анализируются главные факторы и еe причины, дается оценка сегодняшней ситуации. В настоящее время это одна из главных проблем, требующая немедленного решения. Основная причина деградации лесов человеческий фактор. Особую роль сыграли нерегулируемые и незаконные рубки лесов 1990-х и начала 2000-х г. Представлены разные апробированные подходы и методы для реконструкции и восстaновления деградированных лесов РА.
Keywords: Agriculture; Forestry